Spatial subsetting enables integrative modeling of oral squamous cell carcinoma multiplex imaging data - Jakob Einhaus; Dyani K. Gaudilliere; Julien Hedou; Dorien Feyaerts; Michael G. Ozawa; Masaki Sato; Edward A. Ganio; Amy S. Tsai; Ina A. Stelzer; Karl C. Bruckman; Jonas N. Amar; Maximilian Sabayev; et al. (iScience, 2023)
Summary: Oral squamous cell carcinoma (OSCC), a prevalent and aggressive neoplasm, poses a significant challenge due to poor prognosis and limited prognostic biomarkers. Leveraging highly multiplexed imaging mass cytometry, we investigated the tumor immune microenvironment (TIME) in OSCC biopsies, characterizing immune cell distribution and signaling activity at the tumor-invasive front. Our spatial subsetting approach standardized cellular populations by tissue zone, improving feature reproducibility and revealing TIME patterns accompanying loss-of-differentiation. Employing a machine-learning pipeline combining reliable feature selection with multivariable modeling, we achieved accurate histological grade classification (AUC = 0.88). Three model features correlated with clinical outcomes in an independent cohort: granulocyte MAPKAPK2 signaling at the tumor front, stromal CD4+ memory T cell size, and the distance of fibroblasts from the tumor border. This study establishes a robust modeling framework for distilling complex imaging data, uncovering sentinel characteristics of the OSCC TIME to facilitate prognostic biomarkers discovery for recurrence risk stratification and immunomodulatory therapy development.